Pengaruh Budaya Kerja dan Kepemimpinan Kerja terhadap Kinerja Pegawai - Fadhillah, Fadli; Kamil, Musthafa (Universitas 17 Agustus 1945 Semarang, 2024)
Fadli Fadhillah (64201182). The Effect of Work Culture and Leadership on the Performance of Government Employees, Depok City Manpower Office. The research was conducted at the Depok City Manpower Office Government by distributing questionnaires directly to obtain primary data. The effect of work culture and work leadership on employee performance at the Depok City Manpower Office Government. This study aims to see how the impact of work culture and work leadership together on employee performance at the Depok City Manpower Office. The sample in this study was all the population of 38 respondents. This research is quantitative by testing the hypothesis using SPSS 27. The t test results show that the work culture variable has a significant positive effect on employee performance. The t test results show that the work leadership variable has a significant positive effect on employee performance. The results of the f test show that work culture and work leadership have a positive and significant effect simultaneously on employee performance.